2014
DOI: 10.1101/gr.173518.114
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput functional testing of ENCODE segmentation predictions

Abstract: The histone modification state of genomic regions is hypothesized to reflect the regulatory activity of the underlying genomic DNA. Based on this hypothesis, the ENCODE Project Consortium measured the status of multiple histone modifications across the genome in several cell types and used these data to segment the genome into regions with different predicted regulatory activities. We measured the cis-regulatory activity of more than 2000 of these predictions in the K562 leukemia cell line. We tested genomic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
346
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(386 citation statements)
references
References 40 publications
36
346
0
4
Order By: Relevance
“…High-resolution mapping of numerous histone modifications in multiple cell types contributed to detection of most common combinations and associated functional genomic elements [62][63][64] and allowed segmentation of the genome into distinct domains based on the levels of various modifications [62,63,65]. Although specific histone modification combinations generally reflect the identity of the underlying DNA element, recent study has shown that actual levels of modification do not necessarily reflect the predicted regulatory activity [66].…”
Section: Promoters Are Marked By Specific Histone Modificationsmentioning
confidence: 99%
“…High-resolution mapping of numerous histone modifications in multiple cell types contributed to detection of most common combinations and associated functional genomic elements [62][63][64] and allowed segmentation of the genome into distinct domains based on the levels of various modifications [62,63,65]. Although specific histone modification combinations generally reflect the identity of the underlying DNA element, recent study has shown that actual levels of modification do not necessarily reflect the predicted regulatory activity [66].…”
Section: Promoters Are Marked By Specific Histone Modificationsmentioning
confidence: 99%
“…Recently, Kwasnieski et al (2014) used a massively parallel reporter gene assay (MPRA) to compare the enhancer activity of genomic regions in different chromatin states in K562 cells. We adopted a similar approach to compare H2BK20ac-only and H3K27ac-only enhancers.…”
Section: Genome-wide Pattern Of H2bk20ac At Different Enhancer Classesmentioning
confidence: 99%
“…This assay is based upon the well-established reporter gene assay, in which a vector containing a reporter gene (e.g. luciferase or green fluorescent protein [GFP]), a promoter and a potential regulatory sequence is inserted into a plasmid, which is transfected into a cell; sequences that regulate gene expression then alter the amount of luciferase/GFP expressed (Arnold et al, 2013;Melnikov et al, 2012;Ow et al, 1986;Patwardhan et al, 2012;Vockley et al, 2015;Kwasnieski et al, 2014). Through the use of unique barcodes in the 3′ untranslated region (UTR) of the reporter to differentiate expression of individual oligos, MPRA can test many different sequences simultaneously, and it has been shown to reproducibly detect segments of the genome that change expression levels (Kheradpour et al, 2013;Mogno et al, 2013).…”
Section: Introductionmentioning
confidence: 99%